A integração de fornecedores no processo de desenvolvimento de novos produtos na indústria de alimentos - Ayque de Meira, Maria Luiza Bernardes; Rotondaro, Roberto (Revista Gestão da Produção Operações e Sistemas, 2006)
The partnership between clients and suppliers is becoming common in the new product developmentprocess, mainly in competitive markets that demand low prices, high quality and availability. Successful factorsare communication, reliability and commitment. In the food industry, the relation with suppliers during thedevelopment process for new products allows for the access to technology and innovation, project cycle timereduction as well as a good cost-efficiency.Keywords: Client-Supplier Partnership; Food Product Development; Outsourcing.